Moonlighting with WDR5: A Cellular Multitasker - Guarnaccia, Alissa duPuy (J Clin Med, 2018)
WDR5 is a highly conserved WD40 repeat-containing protein that is essential for proper regulation of multiple cellular processes. WDR5 is best characterized as a core scaffolding component of histone methyltransferase complexes, but emerging evidence demonstrates that it does much more, ranging from expanded functions in the nucleus through to controlling the integrity of cell division. The purpose of this review is to describe the current molecular understandings of WDR5, discuss how it participates in diverse cellular processes, and highlight drug discovery efforts around WDR5 that may form the basis of new anti-cancer therapies.